485 Laparoscopic assisted infralevator posterior exenteration with vulvovaginal reconstruction. (13th November 2020) - Shylasree, TS; Poddar, P; Bhandare, M; Jaiswal, D; Popat, P; Menon, S
Abstract : Introduction: Recurrent cervical cancer following surgery and pelvic radiotherapy is a complex disease to treat. It is also difficult to differentiate field change cancers of the lower genital tract from recurrent cervical cancer. Exenterative surgery is commonly indicated for central recurrences with no involvement of pelvic side wall structures or lymphnodes as complete resection is feasible with better oncological outcomes. We present a surgical film of a unique case who developed disease (? recurrent/field change cancer) on the vulva with extension to posterior vagina and anal mucosa. Methods: A 50 year old lady presented with a malignant growth on the vulva extending to lower vagina and anal canal. She did not have lateral side wall disease or lymph nodal involvement or distant metastasis. She had undergone non radical hysterectomy for an undiagnosed cervical cancer and had received adjuvant pelvic radiation elsewhere 12 months prior to referral to our hospital. We performed Laparoscopic Assisted Infralevator Posterior Exenteration with Vulvovaginal Reconstruction using V-Y advancement flaps. Results: Her postoperative recovery was uneventful. Histopathology confirmed squamous cell cancer and margins of resection were free of tumor. Two suspicious sub-centimeter nodules in the pelvic peritoneum was positive for tumor for which she received adjuvant chemotherapy. Conclusion: Laparoscopic Assisted Infralevator Posterior Exenteration with Vulvovaginal reconstruction even though a complex procedure facilitates early postoperative recovery and timely administration of adjuvant therapy when indicated.